Local Convergence of an EM-Like Image Reconstruction Method for Diffuse Optical Tomography (Journal of Computational Mathematics, 2018)
In this paper, an EM-like image reconstruction iterative formula specifically developed for stable external sources is rewritten as a map towards a fixed point iteration. Local convergence of the image reconstruction method is then proved. Finally a three-dimensional numerical image reconstruction example is presented.
Keywords: Diffuse optical tomography; Image reconstruction; Fixed-point iteration; Local convergence.